Trust in Effective International Business Cooperation: Mediating Effect of Work Engagement - Małgorzata Chrupała-Pniak; Damian Grabowski; Monika Sulimowska-Formowicz (Entrepreneurial Business and Economics Review, 2017)
Objective: This study aims to analyse the relationships between relational competence and its trust-building processes with individuals’ traits considered as psychological antecedents of inter-organizational relationships (IORs), outcomes. We hypothesize that organizational trust-building competence, situational trust, trust propensity, and autonomous motivation of cooperating teams and their managers influence IORs outcomes through work engagement of cooperating people.